Encuesta Nacional de Tendencias de Fitness en España para 2024 (National Survey of Fitness Trends in Spain for 2024) - Veiga, Oscar L.; Palos, Juan Jose; Valcarce-Torrente, Manel (Retos, 2024)
Palabras clave: encuesta española fitness, tendencias fitness, industria fitness, encuesta ACSMAbstract. This is the eighth edition of the National Surveys of Fitness Trends in Spain, which replicate the methodology of international surveys on global fitness trends developed and promoted by the American College of Sports Medicine (ACSM). Every year since 2017, the objective of this study is to determine the main trends in the Spanish fitness sector based on the results obtained from the survey conducted for 2024, as well as compare these results with those reported in the 2023 national and international surveys. Additionally, the potential current impact of COVID-19 on the sector and the main trends identified by the respondents were also analyzed. The survey was sent to 7,055 professionals related to the fitness sector, resulting in a response rate of 7.2%, that to say 511 professionals (28.3 % women) answered the survey. The five most relevant trends for 2024 were, in descending order: "functional fitness training", "hiring certified professionals", "personal training in small groups", "personal training", and "exercise regulation of fitness professionals". As has been happening in recent editions, the trends in the top-20 in Spain for 2024 were consistent with those reported in 2023, both in the number of coincidences (18 common trends), positions occupied (within the top-10 there were 9 trends common to both surveys), as well as in the top-1 (functional fitness training). Similarly, there was a greater discrepancy between the 2024 Spanish survey and the 2023 international survey, with 6 coincident trends within the top-10, 13 common trends in the top-20 and a clear disparity in relation to the positions occupied. These results confirm, in line with previous editions, the consistency of trends in the Spanish fitness sector and the consequent divergence with international trends.Keywords: Spanish fitness survey, fitness trends, fitness industry, ACSM survey